Risk of tuberculosis among renal transplant recipients receiving rituximab therapy. Issue 6 (28th October 2022) - Chandrashekhar, Praveen; Kaul, Anupma; Bhaduaria, Dharmendra; Prasad, Narayan; Behera, Manas; Kushwaha, Ravi; Patel, Manas; Yachha, Monika; Srivastava, Aneesh
Abstract: Background: Rituximab is an anti‐CD 20 agent used widely in renal transplant recipients. Its use is associated with various infections; however, its association with tuberculosis (TB) is not well established and has not been studied in post renal transplantation patients. Methods: This is a single‐center, retrospective analysis of 56 renal transplant recipients who received rituximab as a part of desensitization protocol or as rescue therapy for rejections and 287 post‐renal transplant patients who did not receive rituximab during the study period from January 2013 to June 2017. The association between use of rituximab and occurance of TB was studied. Other factors associated with TB were also investigated. Results: Baseline characteristics were similar in both the groups. Mean time for occurrence of TB was 18.4 ± 10.6 months after renal transplantation. Rituximab use was not significantly associated with TB or any other infection. Higher number of rejection episodes (60% vs. 32.72%, p = .029) was the only factor associated with greater incidence of TB. However, no specific type of rejection was associated with TB. Use of plasmapheresis in post‐transplant period for treatment of humoral rejections was associated with significantly higher incidence of TB (33.33% vs. 13.41%, p = .031); however, when pre‐transplant plasmapheresis was also considered, there was no significant difference. The choice of induction agent was not associated with higher incidence of TB. Conclusion: Use of rituximab is not associated with higher incidence of TB when compared to other immunosuppressive agents. Routine screening and prophylaxis may not be advisable, especially in a country like India with high prevalence of TB, as it will further delay transplantation and may adversely affect the outcome of the patients.